Studi Visual UI dan UX pada Gim Persona 5 Royal - Hidayah, Alman Fauzan; Rochmawati, Irma (Fakultas Desain Universitas Komputer Indonesia, 2024)
Abstract: This journal discusses the intricacies of User Interface (UI) and User Experience (UX) design introduced in Persona 5 Royal, the definitive edition of the critically acclaimed role-playing game Persona 5. The journal begins by providing an overview of Persona 5 Royal's UI design, highlighting key design features and aspects that contribute to a better and more immersive gaming experience. It analyzes the integration of new features, such as simplified menus, enhanced navigation tools, and refined visual aesthetics, and evaluates their effectiveness in improving player engagement and accessibility. It also provides insights into the strengths and weaknesses of Persona 5 Royal's UI and UX, offering valuable perspectives for designers, developers, and general game enthusiasts. Ultimately, this research seeks to celebrate and appreciate Persona 5 Royal's UI and UX design achievements while providing critical insights into the ongoing evolution of game design in the modern gaming landscape or industry as a whole.